1999
DOI: 10.1121/1.427166
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic phase conjugation by nonlinear piezoelectricity. I. Principle and basic experiments

Abstract: The principle and the basic experimental results of the acoustic phase conjugation by nonlinear piezoelectricity are described. Acoustic phase conjugate waves at frequency are generated as a result of the interaction between incident acoustic waves at and pump electric fields at 2. An original explanation based on the modulation of sound velocity by the electric field together with the concept of time grating is given. Coupling equations for the PZT ceramics as a nonlinear material are derived. Experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…We have realized ultrasonic phase conjugation using nonlinear piezoelectric interactions in LiNbO 3 [1][2][3] and PbZr x Ti 1Àx O 3 (PZT) ceramics. [4][5][6][7][8][9][10] We have also shown that a phase conjugator introduced into an ultrasonic imager can correct the beam deformation and lessen the image deterioration. 2,8) In our previous studies, this method was most effective when soft samples, such as agarose gels, were imaged in the transmission configuration.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…We have realized ultrasonic phase conjugation using nonlinear piezoelectric interactions in LiNbO 3 [1][2][3] and PbZr x Ti 1Àx O 3 (PZT) ceramics. [4][5][6][7][8][9][10] We have also shown that a phase conjugator introduced into an ultrasonic imager can correct the beam deformation and lessen the image deterioration. 2,8) In our previous studies, this method was most effective when soft samples, such as agarose gels, were imaged in the transmission configuration.…”
Section: Introductionmentioning
confidence: 85%
“…It is difficult to make a phase conjugator that has a large volume and a sufficient efficiency, because the nonlinear piezoelectric interaction, the origin of the phase conjugation, is driven by the electric field applied on a finite volume. 1,7) Applying a high electric field to a large volume requires a very high voltage, which is sometimes experimentally unattainable. One can, alternatively, place a phase conjugator very close to the sample surface.…”
Section: Purpose and Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase conjugation was developed first in optics ͑a review is given, e.g., in the book by Zel'dovich et al 3 ͒ and subsequently introduced in acoustics by Bunkin et al 4 The most effective physical mechanisms for acoustic phase conjugation involve parametric modulation of the sound speed in solids through application of electromagnetic fields. [5][6][7][8] These and other methods of acoustic phase conjugation are reviewed by Brysev et al 6 and Ohno et al 7 In principle, perfect reproduction of the incident field by the time-reversed field may be accomplished when the following conditions are met: the mirror is a surface that encloses the source of radiation; the medium is lossless; and inhomogeneous properties of the medium do not vary with time. Although nonlinear propagation does not, by itself, prevent exact field reproduction, it does when amplification is introduced during time reversal, or when shocks are formed and therefore losses occur in either the incident or timereversed fields.…”
Section: Introductionmentioning
confidence: 98%
“…Recent computational and experimental TRA studies in underwater acoustics suggest that TRAs can robustly retrofocus sound on remote sound sources in shallow ocean waters. TRA research has also been pursued in the area of bio-medical ultrasound , 1999, Tanter 1998, Roux et al 1999a), nondestructive evaluation (Chakroun et al 1995, Draeger et al 1998, Yonak & Dowling 1999, and other areas (Draeger et al 1999ab, Ohno et al 1999, Roux et al 1999b). The basic formulation of acoustic time reversal is provided in .…”
Section: Introductionmentioning
confidence: 99%